2020
DOI: 10.1002/ptr.6805
|View full text |Cite
|
Sign up to set email alerts
|

Aurantio‐obtusin improves obesity and insulin resistance induced by high‐fat diet in obese mice

Abstract: Aurantio‐obtusin (AUR) is the main bioactive compound among the anthraquinones, from Cassia seed extract. This study was conducted to identify whether AUR could improve obesity and insulin resistance, induced by a high‐fat diet in obese mice. Mice were fed a high‐fat diet for 6 weeks and were then assigned to the high‐fat diet (HFD) control group, the AUR 5 mg/kg group, or the AUR 10 mg/kg group. AUR improves glucose by activating the expression of PI3K, Akt and GLUT4, GLUT2. AUR altered the expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Interestingly, our results also identified that the inhibition of autophagy by 3-MA completely blocked AO-induced PPARα activation ( Figure 5 ). In addition, previous studies have shown that AO increased the level of PPARγ in white tissues to improve obesity and insulin resistance ( Guo et al, 2021 ), suggesting the potential activities of AO targeting PPAR family proteins. Similarly, we found that PPAR inhibitor GW6471 markedly eliminated AO-induced decreased level of FASN and mature SREBP-1 ( Figure 5E ), indicating AO exerted its lipid-lowering function in a PPARα-related manner.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, our results also identified that the inhibition of autophagy by 3-MA completely blocked AO-induced PPARα activation ( Figure 5 ). In addition, previous studies have shown that AO increased the level of PPARγ in white tissues to improve obesity and insulin resistance ( Guo et al, 2021 ), suggesting the potential activities of AO targeting PPAR family proteins. Similarly, we found that PPAR inhibitor GW6471 markedly eliminated AO-induced decreased level of FASN and mature SREBP-1 ( Figure 5E ), indicating AO exerted its lipid-lowering function in a PPARα-related manner.…”
Section: Discussionmentioning
confidence: 95%
“…All animals were accepted 1 week of adaptive feeding before the experiment and sacrificed after 8-weeks treatment. For in vivo experiments, the doses of AO (5,10 and 15 mg/kg) were selected based on recent publications ( Xu et al, 2019 ; Guo et al, 2021 ). In chronic HFSW experiment (n = 6), mice were divided into five groups: 1) control group (chow diet); 2) NAFLD model group [HFSW, Western diet-42% Kcal from fat and 0.2% cholesterol (TD.88137, Harlan Laboratories, Inc., Indianapolis, IN, United States) plus with a high sugar solution ( d -fructose: 23.1 g/L and d -glucose: 18.9 g/L) in drinking water ( Li et al, 2021 )]; (3–5) HFSW diet with AO administration group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 suggested eight hub therapeutic targets of Cassiae semen as the hub targets for the treatment of hepato-related diseases, including IL6, SLC37A4, ACHE, IL2, PTGS2, PTPN1, and NOS2, linked with 16, 13, 12, 12, 12, 12, and 10 active compounds ( Table S4 ( https://www.jfda-online.com/cgi/editor.cgi?article=3417&window=additional_files&context=journal )). Interestingly, nearly half of the compounds (7 of 16 active ingredients) were experimentally confirmed to possess hepatoprotective effects via regulating IL6 expression, including chrysophanic acid [ 33 ], galangin [ 34 ], emodin [ 32 ], rhein [ 35 ], aurantio-obtusin [ 36 ], aloe emodin [ 37 ], and physcion [ 38 ]. All these findings indicated that Cassiae semen has the hepatoprotective activities through regulating multiple therapeutic targets.…”
Section: Resultsmentioning
confidence: 99%
“…AO can also mitigate nonalcoholic fatty liver disease by promoting autophagy flux via inducing AMPK phosphorylation and promoting fatty acid oxidation [ 33 ]. In addition, AO alleviates obesity by regulating lipid metabolism-related genes and inflammatory cytokines [ 34 ] or by activating PPARα-dependent mitochondrial thermogenesis in brown adipose tissue [ 35 ]. Moreover, AO has the potential to treat hypertension since it can increase nitric oxide production and regulate endothelium integrity by modulating PI3K/Akt/eNOS pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%